Genetic Diversity and Population Structure in Cities Is Not Consistent Among Cosmopolitan Plant Species - Ava M. Hoffman; Jennifer M. Cocciardi; Prothama Manna; Diego F. Alvarado‐Serrano; Jeannine Cavender‐Bares; Peter M. Groffman; Sharon J. Hall; Sarah E. Hobbie; Susannah B. Lerman; Josep Padullés Cubino; Diane E. Pataki; Tara L. E. Trammell; et al. (Molecular Ecology, 2026)
Urbanisation has led to increasing homogenization of plant communities across cities. However, it is unclear whether these patterns extend to cosmopolitan plant species at the genetic level. We examined genome‐wide genetic patterns in six widespread plant species (three Poaceae and three Asteraceae) across five cities in the USA (Boston, Baltimore, Minneapolis‐St. Paul, Phoenix, and Los Angeles) using reduced‐representation sequencing. We assessed genetic structure, differentiation, and patterns of isolation by distance (IBD) and environment (IBE) to determine if species were genetically homogeneous or differentiated by city, percentage of impervious surface, or both. Most species exhibited limited population structure overall, with Poa annua (annual bluegrass), Taraxacum officinale (dandelion), and Cynodon dactylon (Bermuda grass) showing no significant genetic differentiation among cities, a pattern consistent with high gene flow mediated by human activity. Notable exceptions included city‐level differences in Erigeron canadensis (horseweed) and Lactuca serriola (prickly lettuce), especially in Phoenix. We also observed low genetic diversity in Digitaria sanguinalis (crabgrass) from Phoenix, suggesting recent founder effects or selection via environmental filtering. Erigeron canadensis , the only native species studied, displayed stronger differentiation by city, along with significant isolation by temperature and distance. Among all species, we found no evidence for population structure by impervious surface. Our findings indicate that widespread population genetic structure patterns of cosmopolitan plants are likely to depend more on species attributes (e.g., self‐compatibility) and human‐mediated dispersal than on urbanisation per se.

Temporal and Spatial Dynamics of Soil Carbon Cycling and Its Response to Environmental Change in a Northern Hardwood Forest - Sophie F. von Fromm; Connor I. Olson; Matthew D. Monroe; Carlos A. Sierra; Charles T. Driscoll; Peter M. Groffman; Chris E. Johnson; Peter A. Raymond; Caitlin Hicks Pries (Global Change Biology, 2025)
The timescales over which soil carbon responds to global change are a major uncertainty in the terrestrial carbon cycle. Radiocarbon measurements on archived soil samples are an important tool for addressing this uncertainty. We present time series (1969–2023) of radiocarbon measurements for litter (Oi/Oe and Oa/A) and mineral (0–10 cm) soils from the Hubbard Brook Experimental Forest, a predominantly hardwood forest in the northeastern USA. To estimate soil carbon cycling rates, we built different autonomous linear compartmental models. We found that soil litter carbon cycles on decadal timescales (Oi/Oe: ~7 years), whereas carbon at the organic‐mineral interface (Oa/A), and mineral soil (0–10 cm) carbon cycles on centennial timescales (~104 and 302 years, respectively). At the watershed‐level, the soil system appears to be at steady‐state, with no observed changes in carbon stocks or cycling rates over the study period, despite increases in precipitation, temperature, and soil pH. However, at the site‐level, the Oi/Oe is losing carbon (−15 g C m −2 year −1 since 1998). The observed decline in carbon stocks can be detected when the Oi and Oe layers are modeled separately. This pattern suggests that the rapidly cycling litter layer at the smaller scale is responding to recent environmental changes. Our results highlight the importance of litter carbon as an “early‐warning system” for soil responses to environmental change, as well as the challenges of detecting gradual environmental change across spatial scales in natural forest ecosystems.

Lawn management intensity leads to contrasting effects on belowground ecology and turfgrass aesthetic - Hayden W. Bock; Olivia B. Morse; Frank S. Rossi; Peter M. Groffman; Jed P. Sparks; Kyle G. Wickings (Urban Forestry & Urban Greening, 2025)

Feasibility of constructed soils for tree planting – A pilot study in New York City - Saidan Qi; Zhongqi Cheng; Richard Hallett; Sara P. Egendorf; Andrew B. Reinmann; Peter M. Groffman (Urban Forestry & Urban Greening, 2024)

The urgency of building soils for Middle Eastern and North African countries: Economic, environmental, and health solutions - Maha Deeb; Andrey Valentinovich Smagin; Stephan Pauleit; Olivier Fouché-Grobla; Pascal Podwojewski; Peter M. Groffman (Science of The Total Environment, 2024)

Woody Plant–Soil Relationships in Interstitial Spaces Have Implications for Future Forests Within and Beyond Urban Areas - Gisselle A. Mejía; Peter M. Groffman; Meghan L. Avolio; Anika R. Bratt; Jeannine Cavender-Bares; Noortje H. Grijseels; Sharon J. Hall; James Heffernan; Sarah E. Hobbie; Susannah B. Lerman; Jennifer L. Morse; Desiree L. Narango; et al. (Ecosystems, 2024)

Accelerated soil nitrogen cycling in response to a whole ecosystem acid rain mitigation experiment - Richard E. Marinos; Peter M. Groffman; Charles T. Driscoll; Emily S. Bernhardt (Soil Biology and Biochemistry, 2024)

Balancing upland green infrastructure and stream restoration to recover urban stormwater and nitrate load retention - Ruoyu Zhang; Lawrence E. Band; Peter M. Groffman (Journal of Hydrology, 2023)

Spatial and Temporal Patterns of Nitrogen Mobilization in Residential Lawns - Amanda K. Suchy; Peter M. Groffman; Lawrence E. Band; Jonathan M. Duncan; Arthur J. Gold; J. Morgan Grove; Dexter H. Locke; Laura Templeton; Ruoyu Zhang (Ecosystems, 2023)

Long-term trends in nitrate and chloride in streams in an exurban watershed - Emma S. Castiblanco; Peter M. Groffman; Jonathan Duncan; Lawrence E. Band; Edward Doheny; Gary T. Fisher; Emma Rosi; Amanda K. Suchy (Urban Ecosystems, 2023)

Soil microbiomes in lawns reveal land-use legacy impacts on urban landscapes - Grant L. Thompson; Natalie Bray; Peter M. Groffman; Jenny Kao-Kniffin (Oecologia, 2023)
Land-use change is highly dynamic globally and there is great uncertainty about the effects of land-use legacies on contemporary environmental performance. We used a chronosequence of urban grasslands (lawns) that were converted from agricultural and forested lands from 10 to over 130 years prior to determine if land-use legacy influences components of soil biodiversity and composition over time. We used historical aerial imagery to identify sites in Baltimore County, MD (USA) with agricultural versus forest land-use history. Soil samples were taken from these sites as well as from existing well-studied agricultural and forest sites used as historical references by the National Science Foundation Long-Term Ecological Research Baltimore Ecosystem Study program. We found that the microbiomes in lawns of agricultural origin were similar to those in agricultural reference sites, which suggests that the ecological parameters on lawns and reference agricultural systems are similar in how they influence soil microbial community dynamics. In contrast, lawns that were previously forest showed distinct shifts in soil bacterial composition upon recent conversion but reverted back in composition similar to forest soils as the lawns aged over decades. Soil fungal communities shifted after forested land was converted to lawns, but unlike bacterial communities, did not revert in composition over time. Our results show that components of bacterial biodiversity and composition are resistant to change in previously forested lawns despite urbanization processes. Therefore land-use legacy, depending on the prior use, is an important factor to consider when examining urban ecological homogenization.

Urbanization can accelerate climate change by increasing soil N 2 O emission while reducing CH 4 uptake - Yang Zhan; Zhisheng Yao; Peter M. Groffman; Junfei Xie; Yan Wang; Guangtao Li; Xunhua Zheng; Klaus Butterbach‐Bahl (Global Change Biology, 2023)
Urban land‐use change has the potential to affect local to global biogeochemical carbon (C) and nitrogen (N) cycles and associated greenhouse gas (GHG) fluxes. We conducted a meta‐analysis to (1) assess the effects of urbanization‐induced land‐use conversion on soil nitrous oxide (N 2 O) and methane (CH 4 ) fluxes, (2) quantify direct N 2 O emission factors (EF d ) of fertilized urban soils used, for example, as lawns or forests, and (3) identify the key drivers leading to flux changes associated with urbanization. On average, urbanization increases soil N 2 O emissions by 153%, to 3.0 kg N ha −1 year −1 , while rates of soil CH 4 uptake are reduced by 50%, to 2.0 kg C ha −1 year −1 . The global mean annual N 2 O EF d of fertilized lawns and urban forests is 1.4%, suggesting that urban soils can be regional hotspots of N 2 O emissions. On a global basis, conversion of land to urban greenspaces has increased soil N 2 O emission by 0.46 Tg N 2 O‐N year −1 and decreased soil CH 4 uptake by 0.58 Tg CH 4 ‐C year −1 . Urbanization driven changes in soil N 2 O emission and CH 4 uptake are associated with changes in soil properties (bulk density, pH, total N content, and C/N ratio), increased temperature, and management practices, especially fertilizer use. Overall, our meta‐analysis shows that urbanization increases soil N 2 O emissions and reduces the role of soils as a sink for atmospheric CH 4 . These effects can be mitigated by avoiding soil compaction, reducing fertilization of lawns, and by restoring native ecosystems in urban landscapes.

Automated sensor-based quantification of soil water retention and microbial respiration across drying conditions - Huijie Gan; Wayne R. Roper; Peter M. Groffman; Thomas F. Morris; Karl Guillard (Soil Biology and Biochemistry, 2023)

Tracing carbon flow through a sugar maple forest and its soil components: role of invasive earthworms - Timothy Fahey; Patrick Bohlen; Ted R. Feldpausch; Melany Fisk; Marc Goebel; Peter M. Groffman; John Maerz; Joseph Yavitt (Plant and Soil, 2021)

Snowpack affects soil microclimate throughout the year - Geoffrey Wilson; Mark Green; John Brown; John Campbell; Peter Groffman; Jorge Durán; Jennifer Morse (Climatic Change, 2020)

Ecosystem Nitrogen Response to a Simulated Ice Storm in a Northern Hardwood Forest - Julie N. Weitzman; Peter M. Groffman; John L. Campbell; Charles T. Driscoll; Robert T. Fahey; Timothy J. Fahey; Paul G. Schaberg; Lindsey E. Rustad (Ecosystems, 2020)

Changes in long‐term water quality of Baltimore streams are associated with both gray and green infrastructure - Alexander J. Reisinger; Ellen Woytowitz; Emily Majcher; Emma J. Rosi; Kenneth T. Belt; Jonathan M. Duncan; Sujay S. Kaushal; Peter M. Groffman (Limnology and Oceanography, 2019)
The steadily rising global urban population has placed substantial strain on urban water quality, and this strain is projected to increase for the foreseeable future. Considerable attention has been given to the hydrological and physico‐chemical effects of urbanization on stream ecosystems. However, due to the relative infancy of the field of urban ecology, long‐term water quality analyses in urban streams are sparse. Using a 15‐yr stream chemistry monitoring record from Baltimore, Maryland, we quantified long‐term trends in nitrate, phosphate, total nitrogen, total phosphorus, chloride, and sulfate export at several sites along a rural–urban gradient. We found no significant change in solute export at most sites, although we did find specific patterns of interest for certain solutes. For example, nitrogen export declined at the most headwater urban site, while phosphorus export declined at the most downstream urban site. Coupling long‐term monitoring with data on gray and green infrastructure management throughout the landscape, we established relationships between solute export at the most downstream urban monitoring site and sanitary sewer overflows (SSOs), best management practice (BMP) implementation, and road salt application rates. Phosphorus export was correlated with BMP implementation in the watershed, whereas nitrogen export was related to SSOs. Despite highly urbanized watersheds, water quality does not appear to be declining at most of these sites, suggesting that current management may have limited further impairment. Results of our study suggest that both gray and green infrastructure are key for maintaining and improving water quality in this highly urbanized watershed.

Crab Burrowing Limits Surface Litter Accumulation in a Temperate Salt Marsh: Implications for Ecosystem Functioning and Connectivity - Jorge L. Gutiérrez; Clive G. Jones; Pablo D. Ribeiro; Stuart E. G. Findlay; Peter M. Groffman (Ecosystems, 2018)

Nonlinear response of nitric oxide fluxes to fertilizer inputs and the impacts of agricultural intensification on tropospheric ozone pollution in Kenya - Jonathan E. Hickman; Yaoxian Huang; Shiliang Wu; Willy Diru; Peter M. Groffman; Katherine L. Tully; Cheryl A. Palm (Global Change Biology, 2017)
Crop yields in sub‐Saharan Africa remain stagnant at 1 ton ha −1 , and 260 million people lack access to adequate food resources. Order‐of‐magnitude increases in fertilizer use are seen as a critical step in attaining food security. This increase represents an unprecedented input of nitrogen (N) to African ecosystems and will likely be accompanied by increased soil emissions of nitric oxide ( NO ). NO is a precursor to tropospheric ozone, an air pollutant and greenhouse gas. Emissions of NO from soils occur primarily during denitrification and nitrification, and N input rates are a key determinant of emission rates. We established experimental maize plots in western Kenya to allow us to quantify the response function relating NO flux to N input rate during the main 2011 and 2012 growing seasons. NO emissions followed a sigmoid response to fertilizer inputs and have emission factors under 1% for the roughly two‐month measurement period in each year, although linear and step relationships could not be excluded in 2011. At fertilization rates above 100 kg N ha −1 , NO emissions increased without a concomitant increase in yields. We used the geos‐chem chemical transport model to evaluate local impacts of increased NO emissions on tropospheric ozone concentrations. Mean 4‐hour afternoon tropospheric ozone concentrations in Western Kenya increased by up to roughly 2.63 ppbv under fertilization rates of 150 kg N ha −1 or higher. Using AOT 40, a metric for assessing crop damage from ozone, we find that the increased ozone concentrations result in an increase in AOT 40 exposure of approximately 110 ppbh for inputs of 150 kg N ha −1 during the March–April–May crop growing season, compared with unfertilized simulations, with negligible impacts on crop productivity. Our results suggest that it may be possible to manage Kenyan agricultural systems for high yields while avoiding substantial impacts on air quality.

Moving Towards a New Urban Systems Science - Peter M. Groffman; Mary L. Cadenasso; Jeannine Cavender-Bares; Daniel L. Childers; Nancy B. Grimm; J. Morgan Grove; Sarah E. Hobbie; Lucy R. Hutyra; G. Darrel Jenerette; Timon McPhearson; Diane E. Pataki; Steward T. A. Pickett; et al. (Ecosystems, 2017)

Reduced snow cover alters root‐microbe interactions and decreases nitrification rates in a northern hardwood forest - Patrick O. Sorensen; Pamela H. Templer; Lynn Christenson; Jorge Duran; Timothy Fahey; Melany C. Fisk; Peter M. Groffman; Jennifer L. Morse; Adrien C. Finzi (Ecology, 2016)
Snow cover is projected to decline during the next century in many ecosystems that currently experience a seasonal snowpack. Because snow insulates soils from frigid winter air temperatures, soils are expected to become colder and experience more winter soil freeze‐thaw cycles as snow cover continues to decline. Tree roots are adversely affected by snowpack reduction, but whether loss of snow will affect root‐microbe interactions remains largely unknown. The objective of this study was to distinguish and attribute direct (e.g., winter snow‐ and/or soil frost‐mediated) vs. indirect (e.g., root‐mediated) effects of winter climate change on microbial biomass, the potential activity of microbial exoenzymes, and net N mineralization and nitrification rates. Soil cores were incubated in situ in nylon mesh that either allowed roots to grow into the soil core (2 mm pore size) or excluded root ingrowth (50 μm pore size) for up to 29 months along a natural winter climate gradient at Hubbard Brook Experimental Forest, NH ( USA ). Microbial biomass did not differ among ingrowth or exclusion cores. Across sampling dates, the potential activities of cellobiohydrolase, phenol oxidase, and peroxidase, and net N mineralization rates were more strongly related to soil volumetric water content ( P 0.05; R 2 = 0.25–0.46) than to root biomass, snow or soil frost, or winter soil temperature ( R 2 P 0.01; R 2 = 0.28), suggesting that trees compensate for overwinter root mortality caused by soil freezing by re‐allocating resources towards root production. At the sites with the deepest snow cover, root ingrowth reduced nitrification rates by 30% ( P 0.01), showing that tree roots exert significant influence over nitrification, which declines with reduced snow cover. If soil freezing intensifies over time, then greater compensatory root growth may reduce nitrification rates directly via plant‐microbe N competition and indirectly through a negative feedback on soil moisture, resulting in lower N availability to trees in northern hardwood forests.

Effects of Harvesting Forest Biomass on Water and Climate Regulation Services: A Synthesis of Long-Term Ecosystem Experiments in Eastern North America - Jesse Caputo; Colin M. Beier; Peter M. Groffman; Douglas A. Burns; Frederick D. Beall; Paul W. Hazlett; Thad E. Yorks (Ecosystems, 2016)

Climate change impacts on ecosystems and ecosystem services in the United States: process and prospects for sustained assessment - Nancy B. Grimm; Peter Groffman; Michelle Staudinger; Heather Tallis (Climatic Change, 2016)

Climate Variation Overwhelms Efforts to Reduce Nitrogen Delivery to Coastal Waters - Neil D. Bettez; Jonathan M. Duncan; Peter M. Groffman; Lawrence E. Band; Jarlath O’Neil-Dunne; Sujay S. Kaushal; Kenneth T. Belt; Neely Law (Ecosystems, 2015)

Nitrogen supply modulates the effect of changes in drying–rewetting frequency on soil C and N cycling and greenhouse gas exchange - Lourdes Morillas; Jorge Durán; Alexandra Rodríguez; Javier Roales; Antonio Gallardo; Gary M. Lovett; Peter M. Groffman (Global Change Biology, 2015)
Climate change and atmospheric nitrogen (N) deposition are two of the most important global change drivers. However, the interactions of these drivers have not been well studied. We aimed to assess how the combined effect of soil N additions and more frequent soil drying–rewetting events affects carbon (C) and N cycling, soil:atmosphere greenhouse gas ( GHG ) exchange, and functional microbial diversity. We manipulated the frequency of soil drying–rewetting events in soils from ambient and N‐treated plots in a temperate forest and calculated the Orwin & Wardle Resistance index to compare the response of the different treatments. Increases in drying–rewetting cycles led to reductions in soil levels, potential net nitrification rate, and soil : atmosphere GHG exchange, and increases in and total soil inorganic N levels. N‐treated soils were more resistant to changes in the frequency of drying–rewetting cycles, and this resistance was stronger for C‐ than for N‐related variables. Both the long‐term N addition and the drying–rewetting treatment altered the functionality of the soil microbial population and its functional diversity. Our results suggest that increasing the frequency of drying–rewetting cycles can affect the ability of soil to cycle C and N and soil : atmosphere GHG exchange and that the response to this increase is modulated by soil N enrichment.

Hydrologic and Biogeochemical Drivers of Riparian Denitrification in an Agricultural Watershed - Lauren E. McPhillips; Peter M. Groffman; Christine L. Goodale; M. Todd Walter (Water, Air, & Soil Pollution, 2015)

Soil Denitrification Fluxes in a Northern Hardwood Forest: The Importance of Snowmelt and Implications for Ecosystem N Budgets - Jennifer L. Morse; Jorge Durán; Peter M. Groffman (Ecosystems, 2015)

Earthworms Reduce Biotic 15-Nitrogen Retention in Northern Hardwood Forests - Holly A. Ewing; Amy R. Tuininga; Peter M. Groffman; Kathleen C. Weathers; Timothy J. Fahey; Melany C. Fisk; Patrick J. Bohlen; Esteban Suarez (Ecosystems, 2015)

Soil denitrification fluxes from three northeastern North American forests across a range of nitrogen deposition - Jennifer L. Morse; Jorge Durán; Fred Beall; Eric M. Enanga; Irena F. Creed; Ivan Fernandez; Peter M. Groffman (Oecologia, 2015)

“Hotspots” and “Hot Moments” of Denitrification in Urban Brownfield Wetlands - Monica M. Palta; Joan G. Ehrenfeld; Peter M. Groffman (Ecosystems, 2014)

Winter climate change affects growing‐season soil microbial biomass and activity in northern hardwood forests - Jorge Durán; Jennifer L. Morse; Peter M. Groffman; John L. Campbell; Lynn M. Christenson; Charles T. Driscoll; Timothy J. Fahey; Melany C. Fisk; Myron J. Mitchell; Pamela H. Templer (Global Change Biology, 2014)
Understanding the responses of terrestrial ecosystems to global change remains a major challenge of ecological research. We exploited a natural elevation gradient in a northern hardwood forest to determine how reductions in snow accumulation, expected with climate change, directly affect dynamics of soil winter frost, and indirectly soil microbial biomass and activity during the growing season. Soils from lower elevation plots, which accumulated less snow and experienced more soil temperature variability during the winter (and likely more freeze/thaw events), had less extractable inorganic nitrogen (N), lower rates of microbial N production via potential net N mineralization and nitrification, and higher potential microbial respiration during the growing season. Potential nitrate production rates during the growing season were particularly sensitive to changes in winter snow pack accumulation and winter soil temperature variability, especially in spring. Effects of elevation and winter conditions on N transformation rates differed from those on potential microbial respiration, suggesting that N‐related processes might respond differently to winter climate change in northern hardwood forests than C‐related processes.

Winter climate change effects on soil C and N cycles in urban grasslands - Jorge Durán; Alexandra Rodríguez; Jennifer L. Morse; Peter M. Groffman (Global Change Biology, 2013)
Despite growing recognition of the role that cities have in global biogeochemical cycles, urban systems are among the least understood of all ecosystems. Urban grasslands are expanding rapidly along with urbanization, which is expected to increase at unprecedented rates in upcoming decades. The large and increasing area of urban grasslands and their impact on water and air quality justify the need for a better understanding of their biogeochemical cycles. There is also great uncertainty about the effect that climate change, especially changes in winter snow cover, will have on nutrient cycles in urban grasslands. We aimed to evaluate how reduced snow accumulation directly affects winter soil frost dynamics, and indirectly greenhouse gas fluxes and the processing of carbon (C) and nitrogen (N) during the subsequent growing season in northern urban grasslands. Both artificial and natural snow reduction increased winter soil frost, affecting winter microbial C and N processing, accelerating C and N cycles and increasing soil : atmosphere greenhouse gas exchange during the subsequent growing season. With lower snow accumulations that are predicted with climate change, we found decreases in N retention in these ecosystems, and increases in N 2 O and CO 2 flux to the atmosphere, significantly increasing the global warming potential of urban grasslands. Our results suggest that the environmental impacts of these rapidly expanding ecosystems are likely to increase as climate change brings milder winters and more extensive soil frost.

Partitioning of belowground C in young sugar maple forest - Timothy J. Fahey; Joseph B. Yavitt; Ruth E. Sherman; Peter M. Groffman; Guoliang Wang (Plant and Soil, 2013)

Transport of Carbon and Nitrogen Between Litter and Soil Organic Matter in a Northern Hardwood Forest - Timothy J. Fahey; Joseph B. Yavitt; Ruth E. Sherman; Peter M. Groffman; Melany C. Fisk; John C. Maerz (Ecosystems, 2011)

Accumulation of Carbon and Nitrogen in Residential Soils with Different Land-Use Histories - Steve M. Raciti; Peter M. Groffman; Jennifer C. Jenkins; Richard V. Pouyat; Timothy J. Fahey; Steward T. A. Pickett; Mary L. Cadenasso (Ecosystems, 2011)

Winter climate change implications for decomposition in northeastern forests: comparisons of sugar maple litter with herbivore fecal inputs - LYNN M. CHRISTENSON; MYLON J. MITCHELL; PETER M. GROFFMAN; GARY M. LOVETT (Global Change Biology, 2010)
Forests in northeastern North America are influenced by varying climatic and biotic factors; however, there is concern that rapid changes in these factors may lead to important changes in ecosystem processes such as decomposition. Climate change (especially warming) is predicted to increase rates of decomposition in northern latitudes. Warming in winter may result in complex effects including decreased levels of snow cover and an increased incidence of soil freezing that will effect decomposition. Along with these changes in climate, moose densities have also been increasing in this region, likely affecting nutrient dynamics. We measured decomposition and N release from 15 N‐labeled sugar maple leaf litter and moose feces over 20 months in reference and snow removal treatment (to induce soil freezing) plots in two separate experiments at the Hubbard Brook Experimental Forest in New Hampshire, USA. Snow removal/soil freezing decreased decomposition of maple litter, but stimulated N transfer to soil and microbial biomass. Feces decomposed more rapidly than maple litter, and feces N moved into the mineral soil more than N derived from litter, likely due to the lower C : N ratio of feces. Feces decomposition was not affected by the snow removal treatment. Total microbial biomass (measured as microbial N and C) was not significantly affected by the treatments in either the litter or feces plots. These results suggest that increases in soil freezing and/or large herbivore populations, increase the transfer rate of N from plant detritus or digested plants into the mineral soil. Such changes suggest that altering the spatial and temporal patterns of soil freezing and moose density have important implications for ecosystem N cycling.

Grazers and soil moisture determine the fate of added 15NH4 + in Yellowstone grasslands - Holly A. Ewing; Peter M. Groffman; Douglas A. Frank (Plant and Soil, 2010)

Nitrogen uptake and denitrification in restored and unrestored streams in urban Maryland, USA - Carolyn A. Klocker; Sujay S. Kaushal; Peter M. Groffman; Paul M. Mayer; Raymond P. Morgan (Aquatic Sciences, 2009)

Climate Variation and Soil Carbon and Nitrogen Cycling Processes in a Northern Hardwood Forest - Peter M. Groffman; Janet P. Hardy; Melany C. Fisk; Timothy J. Fahey; Charles T. Driscoll (Ecosystems, 2009)

Plant rhizospheric N processes: what we don't know and why we should care - Douglas A. Frank; Peter M. Groffman (Ecology, 2009)
An improved understanding of the rapid nitrogen fluxes that occur in plant rhizospheres has not been adequately incorporated into the study of how soil N availability and plant N uptake control a number of important ecological processes. One reason for this is that current methods that measure N availability do not account for the rapid exchange of resources between roots and their closely associated microbial communities. In this paper, we review the tight interactions between roots and microbes and discuss why ignoring the significance of these interactions has led to unrepresentative estimates of N availability in intact plant communities and an incomplete understanding of the environmental factors that control plant‐available N. We also explain why current standard methods to measure soil N availability do not account for important rhizospheric processes. Finally, we issue a challenge to develop new methods that will estimate soil N transformations in intact plant communities and offer some potential approaches that may help catalyze this effort.

Experimental snowpack reduction alters organic matter and net N mineralization potential of soil macroaggregates in a northern hardwood forest - J. Megan Steinweg; Melany C. Fisk; Benjamin McAlexander; Peter M. Groffman; Janet P. Hardy (Biology and Fertility of Soils, 2008)

Dynamics of nitrous oxide in groundwater at the aquatic–terrestrial interface - TIM J. CLOUGH; KELLY ADDY; DOROTHY Q. KELLOGG; BARBARA L. NOWICKI; ARTHUR J. GOLD; PETER M. GROFFMAN (Global Change Biology, 2007)
Few data are available to validate the Intergovernmental Panel on Climate Change's (IPCC) emission factors for indirect emissions of nitrous oxide (N 2 O). In particular the N 2 O emissions resulting from nitrogen leaching and the associated groundwater and surface drainage (EF5‐g) are particularly poorly characterized. In situ push–pull methods have been used to identify the fate of NO 3 − in the groundwater. In this study, we adapted a previously published in situ denitrification push–pull method to examine the fate of 15 N 2 O introduced into the subsoil–groundwater matrix. Enriched 15 N 2 O was manufactured, added to groundwater via a closed system in the laboratory, and then introduced into the groundwater–subsoil matrix in an upland‐marsh transition zone of a salt marsh and a forested alluvial riparian zone. Conservative tracers (SF 6 and Br − ) and 15 N 2 O were injected into the groundwater and left for 1–4 h after which the groundwater was sampled. Added 15 N 2 O behaved in a conservative manner at one site while the other site showed variability with some injections showing significant consumption (3–8 μg N 2 O‐ 15 N kg −1 soil day −1 ) of 15 N 2 O. Our results show that the fate and dynamics of N 2 O in groundwater are complex and variable and that these dynamics should be considered in the development of improved IPCC inventory calculations.

High Nitrate Retention during Winter in Soils of the Hubbard Brook Experimental Forest - Kristin E. Judd; Gene E. Likens; Peter M. Groffman (Ecosystems, 2007)

Calcium Additions and Microbial Nitrogen Cycle Processes in a Northern Hardwood Forest - Peter M. Groffman; Melany C. Fisk; Charles T. Driscoll; Gene E. Likens; Timothy J. Fahey; Christopher Eagar; Linda H. Pardo (Ecosystems, 2006)

Snow depth, soil freezing, and fluxes of carbon dioxide, nitrous oxide and methane in a northern hardwood forest - PETER M. GROFFMAN; JANET P. HARDY; CHARLES T. DRISCOLL; TIMOTHY J. FAHEY (Global Change Biology, 2006)
Soil–atmosphere fluxes of trace gases (especially nitrous oxide (N 2 O)) can be significant during winter and at snowmelt. We investigated the effects of decreases in snow cover on soil freezing and trace gas fluxes at the Hubbard Brook Experimental Forest, a northern hardwood forest in New Hampshire, USA. We manipulated snow depth by shoveling to induce soil freezing, and measured fluxes of N 2 O, methane (CH 4 ) and carbon dioxide (CO 2 ) in field chambers monthly (bi‐weekly at snowmelt) in stands dominated by sugar maple or yellow birch. The snow manipulation and measurements were carried out in two winters (1997/1998 and 1998/1999) and measurements continued through 2000. Fluxes of CO 2 and CH 4 showed a strong seasonal pattern, with low rates in winter, but N 2 O fluxes did not show strong seasonal variation. The snow manipulation induced soil freezing, increased N 2 O flux and decreased CH 4 uptake in both treatment years, especially during winter. Annual N 2 O fluxes in sugar maple treatment plots were 207 and 99 mg N m −2 yr −1 in 1998 and 1999 vs. 105 and 42 in reference plots. Tree species had no effect on N 2 O or CO 2 fluxes, but CH 4 uptake was higher in plots dominated by yellow birch than in plots dominated by sugar maple. Our results suggest that winter fluxes of N 2 O are important and that winter climate change that decreases snow cover will increase soil:atmosphere N 2 O fluxes from northern hardwood forests.

The Contribution of Crab Burrow Excavation to Carbon Availability in Surficial Salt-marsh Sediments - Jorge L. Gutiérrez; Clive G. Jones; Peter M. Groffman; Stuart E. G. Findlay; Oscar O. Iribarne; Pablo D. Ribeiro; C. Martín Bruschetti (Ecosystems, 2006)

Spatial and Temporal Dynamics of Exotic Earthworm Communities Along Invasion Fronts in a Temperate Hardwood Forest in South-Central New York (USA) - Esteban R. Suárez; Timothy J. Fahey; Peter M. Groffman; Joseph B. Yavitt; Patrick J. Bohlen (Biological Invasions, 2006)

Ecological Thresholds: The Key to Successful Environmental Management or an Important Concept with No Practical Application? - Peter M. Groffman; Jill S. Baron; Tamara Blett; Arthur J. Gold; Iris Goodman; Lance H. Gunderson; Barbara M. Levinson; Margaret A. Palmer; Hans W. Paerl; Garry D. Peterson; N. LeRoy Poff; David W. Rejeski; et al. (Ecosystems, 2006)

Tree species, root decomposition and subsurface denitrification potential in riparian wetlands - Miriam Rotkin-Ellman; Kelly Addy; Arthur J. Gold; Peter M. Groffman (Plant and Soil, 2004)

Nitrogen Fluxes and Retention in Urban Watershed Ecosystems - Peter M. Groffman; Neely L. Law; Kenneth T. Belt; Lawrence E. Band; Gary T. Fisher (Ecosystems, 2004)

Earthworm Invasion, Fine-root Distributions, and Soil Respiration in North Temperate Forests - Melany C. Fisk; Timothy J. Fahey; Peter M. Groffman; Patrick J. Bohlen (Ecosystems, 2004)

Influence of Earthworm Invasion on Redistribution and Retention of Soil Carbon and Nitrogen in Northern Temperate Forests - Patrick J. Bohlen; Derek M. Pelletier; Peter M. Groffman; Timothy J. Fahey; Melany C. Fisk (Ecosystems, 2004)

Exotic Earthworm Invasion and Microbial Biomass in Temperate Forest Soils - Peter M. Groffman; Patrick J. Bohlen; Melany C. Fisk; Timothy J. Fahey (Ecosystems, 2004)

Effects of Exotic Earthworms on Soil Phosphorus Cycling in Two Broadleaf Temperate Forests - Esteban R. Surez; Derek M. Pelletier; Timothy J. Fahey; Peter M. Groffman; Patrick J. Bohlen; Melany C. Fisk (Ecosystems, 2004)

Ecosystem Consequences of Exotic Earthworm Invasion of North Temperate Forests - Patrick J. Bohlen; Peter M. Groffman; Timothy J. Fahey; Melany C. Fisk; Esteban Suarez; Derek M. Pelletier; Robert T. Fahey (Ecosystems, 2004)

Merging aquatic and terrestrial perspectives of nutrient biogeochemistry - Nancy B. Grimm; Sarah E. Gergel; William H. McDowell; Elizabeth W. Boyer; C. Lisa Dent; Peter Groffman; Stephen C. Hart; Judson Harvey; Carol Johnston; Emilio Mayorga; Michael E. McClain; Gilles Pinay (Oecologia, 2003)

Nitrogen Dynamics in Ice Storm-Damaged Forest Ecosystems: Implications for Nitrogen Limitation Theory - Benjamin Z. Houlton; Charles T. Driscoll; Timothy J. Fahey; Gene E. Likens; Peter M. Groffman; Emily S. Bernhardt; Donald C. Buso (Ecosystems, 2003)

Effects of Phragmites australis removal on marsh nutrient cycling - Stuart Findlay; Peter Groffman; Susan Dye (Wetlands Ecology and Management, 2003)

Environmental control of fine root dynamics in a northern hardwood forest - GERALDINE L. TIERNEY; TIMOTHY J. FAHEY; PETER M. GROFFMAN; JANET P. HARDY; ROSS D. FITZHUGH; CHARLES T. DRISCOLL; JOSEPH B. YAVITT (Global Change Biology, 2003)
Understanding how exogenous and endogenous factors control the distribution, production and mortality of fine roots is fundamental to assessing the implications of global change, yet our knowledge of control over fine root dynamics remains rudimentary. To improve understanding of these processes, the present study developed regression relationships between environmental variables and fine root dynamics within a northern hardwood forest in New Hampshire, USA, which was experimentally manipulated with a snow removal treatment. Fine roots (

Nitrogen oxide gas emissions from temperate forest soils receiving long‐term nitrogen inputs - RODNEY T. VENTEREA; PETER M. GROFFMAN; LOUIS V. VERCHOT; ALISON H. MAGILL; JOHN D. ABER; PAUL A. STEUDLER (Global Change Biology, 2003)
From spring 2000 through fall 2001, we measured nitric oxide (NO) and nitrous oxide (N 2 O) fluxes in two temperate forest sites in Massachusetts, USA that have been treated since 1988 with different levels of nitrogen (N) to simulate elevated rates of atmospheric N deposition. Plots within a pine stand that were treated with either 50 or 150 kg N ha −1 yr −1 above background displayed consistently elevated NO fluxes (100–200 µg N m −2 h −1 ) compared to control plots, while only the higher N treatment plot within a mixed hardwood stand displayed similarly elevated NO fluxes. Annual NO emissions estimated from monthly sampling accounted for 3.0–3.7% of N inputs to the high‐N plots and 8.3% of inputs to the Pine low‐N plot. Nitrous oxide fluxes in the N‐treated plots were generally −1 ) of nitrite () were detected in mineral soils from both sites. Kinetic models describing NO production as a function of the protonated form of (nitrous acid [HNO 2 ]) adequately described the mineral soil data. The results indicate that atmospheric deposition may generate losses of gaseous NO from forest soils by promoting nitrification, and that the response may vary significantly between forest types under similar climatic regimes. The lowering of pH resulting from nitrification and/or directly from deposition may also play a role by promoting reactions involving HNO 2 .

The fate of nitrogen in gypsy moth frass deposited to an oak forest floor - Lynn M. Christenson; Gary M. Lovett; Myron J. Mitchell; Peter M. Groffman (Oecologia, 2002)

Endomycorrhizal colonization of Dasiphora floribunda, a native plant species of calcareous wetlands in eastern New York State, USA - Douglas Hoewyk; Cathleen Wigand; Peter M. Groffman (Wetlands, 2001)

Denitrification in a semi-arid grazing ecosystem - Douglas A. Frank; Peter M. Groffman (Oecologia, 1998)

Nitrous oxide production in riparian zones and groundwater - Peter M. Groffman; Arthur J. Gold; Pierre-André Jacinthe (Nutrient Cycling in Agroecosystems, 1998)

Commentary: Successes, Limitations, and Frontiers in Ecosystem Science: Reflections on the Seventh Cary Conference - Michael L. Pace; Peter M. Groffman (Ecosystems, 1998)

Water Quality Functions of Riparian Forest Buffers in Chesapeake Bay Watersheds - Richard Lowrance; Lee S. Altier; J. Denis Newbold; Ronald R. Schnabel; Peter M. Groffman; Judith M. Denver; David L. Correll; J. Wendell Gilliam; James L. Robinson; Russell B. Brinsfield; Kenneth W. Staver; William Lucas; et al. (Environmental Management, 1997)

Ecosystem processes along an urban-to-rural gradient - Mark J. McDonnell; Steward T. A. Pickett; Peter Groffman; Patrick Bohlen; Richard V. Pouyat; Wayne C. Zipperer; Robert W. Parmelee; Margaret M. Carreiro; Kimberly Medley (Urban Ecosystems, 1997)